PB RATIO ANALYSIS OF FORAMINIFERA TO OBSERVE PALEOCEANOGRAPHIC CHANGES DURING HOLOCENE IN ARAFURA SEA - Swasty Aninda Piranti; Luli Gustiantini; Shaska R. Zulivandama; Catur Purwanto; Lia Jurnaliah; Budi Muljana; Rina Zuraida; Sangmin Hyun (Marine Geological Institute of Indonesia, 2022)
Arafura Sea is influenced by several climatic dynamics, it is also a part of the coral triangle that provides most of marine organism diversity of the world. Therefore, this area is an important waters that impact the climatic dynamic so its paleoceanographic changes need to be understood. For that, we analyzed the foraminiferal PB ratio from marine sediment core ARAFURA-24 with a core length of 179 cm, collected from 47.4 m water depth, combined with that of Aru-07, taken from 276 m water depth (core length 152 cm). Both sediment cores were collected from the Arafura Sea using a gravity corer on board Geomarin III. ARAFURA-24 was sub-sampling in every 20 cm interval, while Aru-07 had been prepared in every 10 cm interval. PB Ratio values from ARAFURA-24 and Aru-07 ranged from 0,56% - 7,43% and from 29,89% to 82,66%, respectively. The age model was reconstructed by 14C radiocarbon dating derived from organic sediment, combined with tie points of PB ratio records. The result indicates that ARAFURA-24 has been sedimented since the last 9.7 kyr BP. PB ratio records reveal three maximum sea level rises, which are before 7.4 kyr BP, at 5.86 kyr, and after 3 kyr BP (approximately at 2 kyr BP at Aru-07). From the age model reconstruction, sedimentation during the last 3 kyr BP was relatively slower than that in the older period. It can be concluded that the foraminiferal PB ratio during Late Holocene was not significantly impacted by sedimentation rate (hence detrital influence), in contrast, during Mid-Holocene detrital influence had more impact on the PB ratio record.